DEVELOPMENT OF TOOLS AND SAMPLE GROUPS FOR SURVEYS: A CASE STUDY OF PUBLIC MEDIA IN THAILAND IN EVALUATING ACCESS AND THE ROLE OF PUBLIC MEDIA - Yuranun Tamkarn; Thira Sindecharak; Sutthida Chuanwan; Naphaphat Dechprom; Ekasit Nunbhakdi (PEOPLE: International Journal of Social Sciences, 2025)
This survey research outlines the development of tools, the determination of sample groups for data collection in surveys, the monitoring of media access, and the public’s opinion regarding the role of public media. The tools used in the survey include the following: (1) A survey form for evaluating media access and the role of public media; and (2) Interview guidelines for specific groups. All tools were quality-checked, tested, and refined over three rounds to ensure they were suitable for tracking surveys and monitoring. The sample group for the survey in this research consists of a total of 8,695 people age 15 or over, residing in five regions of Thailand: Bangkok and vicinity, Central Region, Northern Region, Northeastern Region, and Southern Region. The sample includes members of the general population who consume public media, as well as specific groups such as the Voiceless group, Civic Citizen group, and Opinion Leader group. The process of developing the tools and defining sample groups underwent rigorous academic procedures, including three rounds of pre-tests and real-world testing over the course of one year. Results from these tests were reviewed, compared, and adjusted to create a reliable tool for evaluating media access and the role of public media in the third round. After developing the tools and defining the sample groups for the survey, and after real-world testing, a summary and proposal for a tracking survey framework for Thai public media are also presented.